Macrozoobenthic community structure in the mangrove aquatic ecosystem and surrounding area of Pejarakan Village, Bali - Zafirah Aanisah Farih; Samosir Agustinus Mangaratua; Sulistiono Sulistiono; Solihin Iin; Nugroho Thomas; Hestirianoto Totok; Srimariana Endang Sunarwati; Arhatin Risti Endriani; Rastina Rastina; Mubarak Ahmad Shofy; Ismail Ismail (BIO Web of Conferences)
Change in macrozoobenthic community structure is commonly an indicator of aquatic ecosystem disturbance, due to the macrozoobenthic low mobility and relatively long life cycle. This research aims to analyze macrozoobenthic community structure in the mangrove aquatics ecosystem and surrounding area of Pejarakan Village, Bali. We conducted this research at six stations covering a mangrove-vegetated area and a brackish water pond in September 2022, January 2023, September 2023, and January 2024. Macrozoobenthos samples were taken using a VanVeen Grab, and water quality measurements were carried out in situ with a water analysis kit. Data were analyzed using species composition, ecological index, and PCA. The macrozoobenthos at the research location comprised 6 classes and 60 genera. The highest density was in January 2024 (289 ind/m2). The diversity index (H') was low-medium (1.99-3.17), the evenness index (E) was high (0,69- 0,96), and the dominance index (C) was low-medium (0,13-0,38). PCA analysis shows that the distribution of macrozoobenthos was influenced by turbidity/total suspended solid.